PEMBINAAN MAJELIS TAKLIM AL-ATQIYA’ DESA MATANG DANAU KECAMATAN PALOH - Rusiadi Rusiadi; Aslan Aslan (JOURNAL OF COMMUNITY DEDICATION, 2023)
The guidance of the Ta'lim assembly, which is held every month in Matang Danau Village, is one strategy to provide understanding to the community about religion. From the results of the Community Service carried out, there are still many people experiencing dilemmas regarding religion, so it is necessary to provide guidance from relevant religious figures, so that there are no differences in religion that cause divisions.